Analisis Pendapatan dan Kelayakan Usaha Kerupuk Udang di Desa Sungsang I dan II Kecamatan Banyuasin II - Harliani, Desliana Opie; Antoni, Mirza; Adriani, Dessy (Agriculture Faculty of Flores University, 2024)
Sungsang I and Sungsang II villages are tidal areas because they are located on the coast and directly adjacent to the Bangka strait. Sungsang I Village and Sungsang II Village are one of the areas that have abundant marine products in Banyuasin II Regency, one of which is shrimp which is then processed by the local community into crackers in the form of a cottage industry. Until now, socioeconomic research on the income and feasibility of shrimp cracker business in this region is still scant. The purpose of this study is to analyze the amount of income of shrimp cracker entrepreneurs in Sungsang I and Sungsang II Villages and their business feasibility. The results of this study showed that the business income of shrimp crackers amounted to Rp. 960,837.67 per production or Rp. 23,899.14 per kilogram of shrimp crackers. While the R/C value obtained from the shrimp cracker business is 1.92 (R/C value > 1), which means that the shrimp cracker business in Sungsang I and Sungsang II Villages is feasible to run.